Conceptualization and Exploration of Attitude toward Advertising Disclosures and Its Impact on Perceptions of Manipulative Intent. Issue 3 (9th October 2013) - THOMAS, VERONICA L.; FOWLER, KENDRA; GRIMM, PAMELA
<x xml:space="preserve">Abstract</x> Significant research has been conducted in an effort to understand how varying elements of disclosures (e.g., size, placement, complexity) in advertisements impact consumers' abilities to understand and recall the disclosed message. Although it is important to research the effectiveness of disclosures, advertisers may have additional concerns if the mere presence of a disclosure impacts consumers' perceptions of the company, advertisement, or brand. Little research currently exists examining the notion of consumers' attitudes toward advertising disclosures or how they might impact the effectiveness of the disclosed message, attitude toward a given communication, or overall evaluation of the brand. We introduce the concept of attitude toward advertising disclosures and develop a scale to measure consumers' attitudes toward disclosed messages. The resultant 14‐item, multidimensional scale is then used to demonstrate how attitude toward advertising disclosures plays a moderating role in influencing consumers' perceptions of manipulative intent.